COMPLIANCE WITH THE 5 PRECEPTS ACCORDING TO THE CONCEPT OF PSYCHOEDUCATION FOR STUDENTS IN GRADE 6 - Yooklunthuan, Weeratana; Apipanyo, Phrapalad Soravit; Vachirapanyo, PhrasamuChokdee; Mererk, Sayyud (Journal of Educational Review Faculty of Education in MCU, 2024)
This research aims 1) to study the level of compliance with the Five Precepts according to the concept of psychoeducation, 2) to compare the compliance with the Five Precepts according to the concept of psychoeducation, and 3) to suggest guidelines for promoting compliance with the Five Precepts according to the concept of psychoeducation. This research is a mixed-method research between qualitative and quantitative research. The samples used in the research were directors, heads of grade levels, teachers, monks who teach morality, guidance teachers, and students. Data were collected by questionnaires and interviews. Data were analyzed using research statistics, including percentages, means, standard deviations, and inferential statistics, namely F-test and t-test. The results of the research found that 1) The level of compliance with the Five Precepts according to the concept of psychoeducation of primary 6 students in general had the highest mean, the level of knowledge and understanding of the Five Precepts was at a high level, and the level of students’ emotions toward the Five Precepts was at a high level, respectively. 2) The results of the comparison between the personal factors of the sample group and the level of compliance with the Five Precepts according to the concept of psychoeducation found that the sample groups with different genders had different levels of support for religious activities in the family. There were different levels of opinions on the practice of the Five Precepts according to the concept of psychoeducation of the 6th grade primary school students. The sample groups with different residences and family statuses did not have different levels of opinions on the practice of the Five Precepts according to the concept of psychoeducation of the 6th grade primary school students. 3) The guidelines for promoting the practice of the Five Precepts according to the concept of psychoeducation consisted of organizing activities based on psychoeducation and projects to instill the Five Precepts, promoting knowledge to students on the practice of observing the Five Precepts, integrating teachings in class, organizing learning activities integrated with the philosophy of the Sufficiency Economy for students to apply in their daily lives, integrating teachings that teach students to be modest, organizing morality and ethics camp activities, instilling in students the benefits of having right speech, and providing monk teachers to teach Buddhism comprehensively.